Foraging Behavior of Heritage versus Desert-Adapted Commercial Rangeland Beef Cows in Relation to Dam-Offspring Contact Patterns - Nyamuryekung’e, Shelemia; Cibils, Andres Francisco; Estell, Richard E.; McIntosh, Matthew; VanLeeuwen, Dawn; Steele, Caitriana; González, Alfredo; Spiegal, Sheri; Continanza, Fatima Guadalupe (Elsevier, 2022)
We compared cow-calf contacts, as well as movement, activity, and pasture use patterns of heritage Raramuri Criollo (RC) and desert-adapted commercial Angus Hereford crossbred (AH) beef cattle grazing Chihuahuan Desert pastures during 4 wk in the summers of 2016 and 2017. Within each herd of 11 cow-calf pairs, a group of 7−9 randomly selected cows were fitted with Global Positioning System collars that recorded animal position at 10-min intervals. Proximity loggers configured to record contact events (< 1-m radius) were fitted on a subset of five cow-calf pairs of each breed. The effect of breed on cow-calf contacts, as well as the dams’ movement, activity, and pasture use patterns were analyzed via mixed analysis of variance models. A higher number of RC cow-calf contacts occurred while the dam was grazing and traveling compared with AH counterparts (P ≤ 0.05). No breed-related differences were observed in the overall number and duration of cow-calf contact events. Compared with AH dams, RC cows traveled farther each day (RC: 7.51 vs. AH: 4.85 km, P < 0.01) at higher movement velocities (5.46 vs. 3.53 m. min−1, P < 0.01) and spent more time traveling (1.05 vs. 0.48 h, P < 0.01), more time grazing (9.37 vs. 7.45 h, P < 0.01), and less time resting (13.07 vs. 15.68 h, P < 0.01). RC cows explored almost three times more daily area than AH (152.30 vs. 57.69 ha, P = 0.01) but spent similar amounts of time within 200 m and 100 m of a drinker. RC calves explored larger daily areas than their AH counterparts (83.0 vs. 20.8 ha, P = 0.05), but no breed differences were detected in the number of contact events near drinkers. RC calves possibly impose fewer constraints on their dams’ movement and activity patterns compared with commonly used British crossbreds when grazing the Chihuahuan Desert during summer.